Peran Social Media Marketing dan Influencer Marketing dalam Upaya Meningkatkan Minat Beli Konsumen pada Produk UMKM Raffas Kitchen Indramayu - Yudianto, Agus; Nurpratama, Meddy; Firdaus, Taufansyah; Sonjaya, Nana Supriatna (Jurnal EMT KITA, 2026)
The purpose of this study is to examine how consumer interest in purchasing from Raffas Kitchen MSMEs in Indramayu is impacted by social media marketing and influencer marketing tactics. The study employs an explanatory research strategy and a quantitative methodology. Using a purposive sampling strategy, questionnaires were given to 47 respondents in order to gather data. With indicators like online communities, interaction, accessibility, and credibility, the results show that the social media variable has a considerable impact on consumers' desire in making a purchase. However, because of low levels of interaction and a mismatch between the target market and the audience, the influencer marketing variable does not demonstrate a meaningful impact. Evaluation of the measurement model shows that all indicators are valid, with AVE surpassing 0.5, loading factor values over 0.70, and composite reliability above 0.7. A 0.521 R-squared value suggestsindicated 52.1% of the variation in customer purchasing interest can be explained by social media and influencer marketing combined. To increase the efficacy of marketing strategies, this study suggests choosing more appropriate influencers and optimizing social media content.